A valorização da criatividade no mercado de consumo de vestuário na contemporaneidade. - Bresani, Mirella Campello (2023)
The present project deals with the planning and prototyping of a product that seeks to solve problems about consumption values linked to the creative economy of clothing and the (re)emergence of the “human raw material” - creatives inserted in the handmade of clothing, identified in observations of the craft day by day and in surveys carried out among professionals and entrepreneurs in the State of Pernambuco. Over the last few decades, new business structures have emerged and the return of excluded and/or marginalized crafts, increasingly since the Industrial Revolution in England, in the last decades of the 18th century, has brought to light business opportunities with lucrative purposes that are becoming making livelihoods, usually coming from craftsmen from different segments of the area studied, giving rise to entrepreneurship and artisanal return. However, it takes advantage of these perceptions of the exponential growth of knowhow to creation, with the aim of solving problems in the area of communication. Handmade, as the translation of the term itself, means the creation and development of products made in an artisanal and/or artistic way, without industrial processes in their entirety, automated and created in series. Bibliography was used in the area of clothing, management, technology and history, to briefly understand and open a field of study and investigation, as well as proposing solutions for communication strategies, thus allowing to identify their stories, people involved in their productions, their values , its purposes and processes, thus achieving a visible and differentiated inauthenticity of the creative economy. Therefore, research was necessary, both bibliographical and marketing: field research in an existing group, for a better understanding and analysis of data, guidance and planning in the face of tools created by Löbach (2001). Among other options arising from brainstorming, the conclusion was reached, although in the case of creation, fashion and design, the final product was determined on prerogatives linked to management, marketing and communication, that the product would have greater efficiency by taking advantage of the sales technology and connections: an application with the aim of connecting the three audiences involved, entrepreneurs/brands, craftsmen and the consumer public with a performance to promote the appreciation of handmade products, interaction between craftsmen and brands with interests in networking and sales. The project is interested in market evolution, along with the development of the application.